A method for liquid-phase exfoliation of two-dimensional porphyrin covalent organic framework nanosheets via a protonation strategy
By protonating a block two-dimensional porphyrin covalent organic frame in an aqueous methanesulfonic acid solution, and using electrostatic repulsion to promote peeling, the problems of low preparation efficiency and poor thickness selectivity of two-dimensional porphyrin covalent organic frame nanosheets in the prior art are solved, and high-efficiency and low-cost large-scale preparation of high-quality nanosheets are achieved.
Patent Information
- Application Number
- CN202411780158.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-05
AI Technical Summary
It is difficult to efficiently prepare high-quality two-dimensional porphyrin covalent organic frame nanosheets in the prior art, and have low yields and poor thickness selectivity.
Liquid phase peeling is performed in aqueous methanesulfonic acid solution through protonation strategy, and imine N in the covalent organic framework of protonated bulk two-dimensional porphyrin and N in the porphyrin center are positively charged, which weakens the interlayer interaction force and promotes peeling.
The efficient preparation of small-layer two-dimensional porphyrin covalent organic frame nanosheets was achieved, with a yield of up to 63.1%, and the proportion of nanosheets with thicknesses less than 2nm was as high as 97.1%, and the dispersion had ultra-high stability.
Smart Images

Figure CN119219940B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of covalent organic framework (COFs) high-efficiency liquid phase exfoliation methods, and specifically relates to a method for liquid phase exfoliation of two-dimensional porphyrin covalent organic framework nanosheets through a protonation strategy. Background Art
[0002] Covalent organic frameworks (COFs) are porous organic polymers constructed from non-metallic elements such as C, N, B, and O through organic linkers with strong covalent bonds and symmetrical arrangement. Porphyrin-based COFs combine the structural advantages of COFs and the light-harvesting properties of porphyrins, and therefore show great application potential in photoresponsive materials. However, the solubility and processability of bulk two-dimensional porphyrin COFs are poor, which greatly limits their further application. In contrast, two-dimensional porphyrin COF nanosheets (CONs) have better dispersion stability in solvents due to the exposure of more active sites, thus further expanding their application areas. At present, the main methods for preparing COF nanosheets include interfacial synthesis, electrochemical exfoliation, mechanical exfoliation, and liquid phase exfoliation. The first three preparation methods all have their disadvantages, and the liquid phase exfoliation method is considered to be a simple, low-cost, large-scale method for preparing covalent organic framework nanosheets. However, there are few studies on the liquid phase exfoliation of two-dimensional covalent organic frameworks, especially the liquid phase exfoliation of two-dimensional porphyrin covalent organic frameworks, and the yield of the prepared covalent organic framework nanosheets is relatively low and the thickness selectivity is relatively poor. Therefore, it is necessary to develop a new method for preparing two-dimensional porphyrin covalent organic framework nanosheets by liquid phase exfoliation with high efficiency, high quality and low cost.
[0003] At present, the relevant patent documents about liquid phase stripping are as follows: The patent document of CN114539547A discloses a method for preparing covalent organic framework nanoparticles, mixing an imine covalent organic framework, a monofunctional competitive monomer and an organic solvent, and performing molecular exchange under ultrasonic action to obtain covalent organic framework nanoparticles, wherein the organic solvent is one or more of ethanol, DMSO, DMF or THF; the patent technology discloses that the imine covalent organic framework and aniline are stripped in the presence of an organic solvent to obtain P-COF nanoparticles, which has general applicability to imine covalent organic frameworks, but there is no relevant record of liquid phase stripping of two-dimensional porphyrin covalent organic frameworks containing specific functional groups and relatively complex molecular structures. The patent document of CN105129784A discloses a method for preparing graphene nanosheets by ultrasonic liquid phase stripping of graphite using methanesulfonic acid as a solvent, and the method is based on the strong interaction between methanesulfonic acid and graphene, so that graphene has a higher concentration and stripping rate in methanesulfonic acid. This patented technology does not contain any relevant records regarding the liquid phase exfoliation of two-dimensional porphyrin covalent organic frameworks containing specific functional groups and relatively complex molecular structures, nor does it contain any relevant records regarding the efficient liquid phase exfoliation of two-dimensional porphyrin covalent organic frameworks through a protonation strategy using an aqueous solution of methanesulfonic acid as a solvent. Summary of the invention
[0004] The technical problem solved by the present invention is to provide a method for liquid-phase exfoliation of two-dimensional porphyrin covalent organic framework nanosheets through a protonation strategy, which is simple to operate, low-cost, large-scale, high-quality and efficient. The method protonates the imine N and the N at the porphyrin center in the bulk two-dimensional porphyrin covalent organic framework to make the material positively charged, thereby weakening the interaction force between the bulk material layers, promoting the exfoliation of the bulk material, and finally realizing the efficient preparation of few-layer two-dimensional porphyrin covalent organic framework nanosheets.
[0005] The present invention adopts the following technical scheme to solve the above technical problems, which is a method for liquid phase exfoliation of two-dimensional porphyrin covalent organic framework nanosheets by protonation strategy, and the specific steps are: placing a bulk material two-dimensional porphyrin covalent organic framework in a methanesulfonic acid aqueous solution for water bath ultrasonic liquid phase exfoliation, and then centrifugally washing and drying the dispersion to obtain a two-dimensional porphyrin covalent organic framework nanosheet, wherein the bulk material two-dimensional porphyrin covalent organic framework is H2P-Bph-COF, TAPP-H, TAPP-Br, TAPP-OMe or TAPP-OH, and the corresponding structural formula is:
[0006]
[0007] It is further defined that the feed ratio of the block material two-dimensional porphyrin covalent organic framework to the methanesulfonic acid aqueous solution is 1 mg: 1-1.2 mL, and the concentration of the methanesulfonic acid aqueous solution is 0.6-1 mol / L.
[0008] It is further defined that the temperature of the water bath ultrasonic liquid phase stripping is 20-30°C.
[0009] It is further defined that the ultrasonic power of the water bath ultrasonic liquid phase stripping is 280 to 400 W, and the ultrasonic time is 5 to 11 hours.
[0010] It is further defined that the centrifugal washing includes two processes: low-speed centrifugal washing and high-speed centrifugal washing, wherein the centrifugal speed of the low-speed centrifugal washing is 1500-2500 rpm, the centrifugal time is 5-15 min, the centrifugal washing is performed 2-3 times, and the centrifugal washing solvent is a mixed solvent of water and ethanol; the upper layer of the dispersion is taken for high-speed centrifugal washing again, the centrifugal speed of the high-speed centrifugal washing is 10000-20000 rpm, the centrifugal time is 3-10 min, and the centrifugal washing solvent is a mixed solvent of water and ethanol; the bottom precipitate is collected and washed with secondary water at least 10 times and ethanol at least 3 times to remove residual methane sulfonic acid, and finally the washed precipitate is vacuum dried at 30-50°C to obtain pure two-dimensional porphyrin covalent organic framework nanosheets.
[0011] Compared with the prior art, the present invention has the following advantages and beneficial effects: the present invention utilizes the acidity of the methanesulfonic acid aqueous solution to protonate the imine N and the N in the porphyrin center in the bulk material two-dimensional porphyrin covalent organic framework and carry a positive charge, thereby forming an electrostatic repulsion between the bulk material layers, which is conducive to weakening the interlayer force of the bulk material two-dimensional porphyrin covalent organic framework. In addition, the functional groups contained in the bulk material two-dimensional porphyrin covalent organic framework also have a certain influence on the stripping. The greater the steric hindrance, the relatively smaller the interaction force between the material layers, which is conducive to the efficient preparation of nanosheets. The addition of the methanesulfonic acid aqueous solution in the present invention greatly promotes the dispersion of the bulk material two-dimensional porphyrin covalent organic framework in water, so that the nanosheet dispersion obtained by stripping has ultra-high stability. The invention has a simple operation process and can prepare a few-layer two-dimensional porphyrin covalent organic framework nanosheet at low cost and on a large scale, wherein the lateral dimensions of the nanosheets obtained by stripping in a methanesulfonic acid aqueous solution are mostly distributed in 1-2 μm; the invention optimizes the concentration, ultrasonic power and ultrasonic time of the methanesulfonic acid aqueous solution by a control variable method, and the yield of the two-dimensional porphyrin covalent organic framework nanosheets stripped by liquid phase under the optimal conditions is as high as 63.1%, and the proportion of nanosheets with a thickness less than 2 nm is as high as 97.1%. Compared with the traditional preparation method of the covalent organic framework nanosheet, the invention has the advantages of simple preparation process, low cost, large-scale and high-quality preparation of the two-dimensional porphyrin covalent organic framework nanosheet, etc. The two-dimensional porphyrin covalent organic framework nanosheet dispersion prepared by the invention can exist stably and is not easy to precipitate, and the absolute value of the Zeta potential of the dispersion obtained by water bath ultrasound is greater than 30 mV. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 The FT-IR spectra and XRD spectra of the TAPP-Br nanosheets and bulk materials obtained by exfoliation in a methanesulfonic acid aqueous solution in Example 3 are shown.
[0013] Figure 2 to Figure 6 AFM and thickness statistics of H2P-Bph-COF, TAPP-H, TAPP-Br, TAPP-OMe and TAPP-OH nanosheets prepared in methanesulfonic acid aqueous solution in Examples 1 to 5, respectively.
[0014] Figure 7 This is a SEM comparison image of TAPP-Br nanosheets and bulk materials prepared in methanesulfonic acid aqueous solution in Example 3.
[0015] Figure 8 TEM comparison of TAPP-Br nanosheets and bulk materials prepared in methanesulfonic acid aqueous solution in Example 3.
[0016] Fig. 9 This is a comparison of the dispersion of bulk materials H2P-Bph-COF, TAPP-H, TAPP-Br, TAPP-OMe and TAPP-OH in methane sulfonic acid aqueous solution and pure water.
[0017] Fig.10 This is a comparison chart of the FT-IR spectra of the protonated TAPP-OMe and its bulk material prepared in an aqueous methanesulfonic acid solution in Example 4.
[0018] Fig.11 This is the UV-visible absorption spectrum of the protonated TAPP-OMe prepared in methanesulfonic acid aqueous solution in Example 4. DETAILED DESCRIPTION
[0019] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention.
[0020] Example 1
[0021] Preparation of H2P-Bph-COF nanosheets
[0022] 1. Weigh 10 mg of bulk material H2P-Bph-COF and disperse it in 10 mL of 0.8 mol / L methanesulfonic acid aqueous solution, and stir at room temperature for 10 min to evenly disperse the bulk material.
[0023] 2. Place the evenly dispersed bulk material H2P-Bph-COF in a 20 mL glass bottle for water bath ultrasound. The ultrasound time is 11 h, the ultrasound power is 280 W, and the water bath ultrasound temperature is maintained at 25 ° C to obtain a dark green suspension.
[0024] 3. The suspension obtained by ultrasound was transferred into a 5 mL centrifuge tube and centrifuged twice at a speed of 2000 rpm, each time for 10 min. The supernatant collected was the H2P-Bph-COF nanosheet dispersion obtained by exfoliation.
[0025] 4. Centrifuge the obtained dispersion at a speed of 18000 rpm for 10 min. The precipitate after centrifugation is H2P-Bph-COF nanosheets. Then wash the nanosheets with secondary water for more than ten times to remove residual methane sulfonic acid, and finally wash them twice with ethanol. Put the washed precipitate in a vacuum drying oven at 40°C overnight to obtain relatively pure H2P-Bph-COF nanosheets.
[0026] Example 2
[0027] Preparation of TAPP-H nanosheets
[0028] 1. Weigh 10 mg of bulk material TAPP-H and disperse it in 10 mL of 1 mol / L methanesulfonic acid aqueous solution, and stir at room temperature for 10 min to evenly disperse the bulk material.
[0029] 2. Place the evenly dispersed bulk material TAPP-H in a 20 mL glass bottle for water bath ultrasound. The ultrasound time is 5 h, the ultrasound power is 320 W, and the water bath ultrasound temperature is maintained at 25 °C to obtain a dark green suspension.
[0030] 3. The suspension obtained by ultrasound was transferred into a 5 mL centrifuge tube and centrifuged twice at 2000 rpm for 10 min each time. The supernatant collected was the TAPP-H nanosheet dispersion obtained by peeling.
[0031] 4. The obtained dispersion was centrifuged at 18000 rpm for 10 min. The precipitate after centrifugation was TAPP-H nanosheets. The nanosheets were then washed with secondary water for more than ten times to remove residual methane sulfonic acid, and finally washed twice with ethanol. The washed precipitate was placed in a vacuum drying oven at 40°C overnight to obtain relatively pure TAPP-H nanosheets.
[0032] Example 3
[0033] Preparation of TAPP-Br nanosheets
[0034] 1. Weigh 10 mg of bulk material TAPP-Br and disperse it in 10 mL of 0.6 mol / L methanesulfonic acid aqueous solution. Stir at room temperature for 10 min to evenly disperse the bulk material.
[0035] 2. Place the evenly dispersed bulk material TAPP-Br in a 20 mL glass bottle for water bath ultrasound. The ultrasound time is set to 11 h, the ultrasound power is 280 W, and the water bath ultrasound temperature is maintained at 25 °C to obtain a dark green suspension.
[0036] 3. The suspension obtained by ultrasound was transferred into a 5 mL centrifuge tube and centrifuged twice at a speed of 2000 rpm, each time for 10 min. The supernatant collected was the TAPP-Br nanosheet dispersion obtained by peeling.
[0037] 4. The obtained dispersion was centrifuged at a speed of 18000 rpm for 10 min. The precipitate after centrifugation was TAPP-Br nanosheets. The nanosheets were then washed with secondary water for more than ten times to remove residual methane sulfonic acid, and finally washed twice with ethanol. The washed precipitate was placed in a vacuum drying oven at 40°C overnight to obtain relatively pure TAPP-Br nanosheets.
[0038] Example 4
[0039] Preparation of TAPP-OMe nanosheets
[0040] 1. Weigh 10 mg of bulk material TAPP-OMe and disperse it in 10 mL of 1 mol / L methanesulfonic acid aqueous solution, and stir at room temperature for 10 min to evenly disperse the bulk material.
[0041] 2. Place the evenly dispersed bulk material TAPP-OMe in a 20 mL glass bottle for water bath ultrasound. The ultrasound time is 9 h, the ultrasound power is 400 W, and the water bath ultrasound temperature is maintained at 25 °C to obtain a dark green suspension.
[0042] 3. The suspension obtained by ultrasound was transferred into a 5 mL centrifuge tube and centrifuged twice at 2000 rpm for 10 min each time. The supernatant collected was the TAPP-OMe nanosheet dispersion obtained by exfoliation.
[0043] 4. The obtained dispersion was centrifuged at a speed of 18000 rpm for 10 min. The precipitate after centrifugation was TAPP-OMe nanosheets. The nanosheets were then washed with secondary water for more than ten times to remove residual methane sulfonic acid, and finally washed twice with ethanol. The washed precipitate was placed in a vacuum drying oven at 40°C overnight to obtain relatively pure TAPP-OMe nanosheets.
[0044] Example 5
[0045] Preparation of TAPP-OH nanosheets
[0046] 1. Weigh 10 mg of bulk material TAPP-OH and disperse it in 10 mL of 0.8 mol / L methanesulfonic acid aqueous solution, and stir at room temperature for 10 min to evenly disperse the bulk material.
[0047] 2. Place the evenly dispersed bulk material TAPP-OH in a 20 mL glass bottle for water bath ultrasound. The ultrasound time is set to 7 h, the ultrasound power is 400 W, and the water bath ultrasound temperature is maintained at 25 °C to obtain a dark green suspension.
[0048] 3. The suspension obtained by ultrasound was transferred into a 5 mL centrifuge tube and centrifuged twice at a speed of 2000 rpm, each time for 10 min. The supernatant collected was the TAPP-OH nanosheet dispersion obtained by peeling.
[0049] 4. The obtained dispersion was centrifuged at a speed of 18000 rpm for 10 min. The precipitate after centrifugation was TAPP-OH nanosheets. The nanosheets were then washed with secondary water for more than ten times to remove residual methane sulfonic acid, and finally washed twice with ethanol. The washed precipitate was placed in a vacuum drying oven at 40°C overnight to obtain relatively pure TAPP-OH nanosheets.
[0050] Table 1 shows the yield of nanosheets obtained by optimizing the concentration of methanesulfonic acid, ultrasonic power and ultrasonic time by the control variable method of the present invention. Among them, the yield of nanosheets obtained when the bulk material TAPP-H is peeled in a methanesulfonic acid aqueous solution is the highest, reaching 63.1%.
[0051] Table 1
[0052]
[0053] Figure 1 The FT-IR spectra and XRD spectra of TAPP-Br nanosheets obtained by exfoliation in methanesulfonic acid aqueous solution and its bulk material. Compared with the bulk material, the characteristic peak (C=N) of the nanosheet exists and its position does not change, indicating that the chemical structure of the two-dimensional porphyrin covalent organic framework nanosheet remains unchanged after exfoliation. However, compared with the bulk material, the crystal form of the nanosheet disappears after exfoliation, which is due to the more disordered stacking of the layered material, and also indicates that this method successfully exfoliates the bulk material into thinner nanosheets.
[0054] Figure 2 to Figure 6The AFM and thickness statistics of H2P-Bph-COF, TAPP-Br, TAPP-OH, TAPP-H and TAPP-OMe nanosheets prepared in methanesulfonic acid aqueous solution. It can be seen from the figure that the lateral size of the nanosheets obtained by exfoliation of the five two-dimensional porphyrin COFs in the methanesulfonic acid aqueous solution system is 1-2μm, and the exfoliation yield of TAPP-H is as high as 63.1%. In addition, among the five two-dimensional porphyrin COFs nanosheets, the selectivity of nanosheets with a thickness of less than 2nm is as high as 97.1%.
[0055] Figure 7 The SEM comparison of TAPP-Br nanosheets and bulk materials prepared in methanesulfonic acid aqueous solution. The COF nanosheets obtained by exfoliation in methanesulfonic acid aqueous solution are all in the form of fragments, and the lateral size of the nanosheets is significantly reduced compared with the bulk material.
[0056] Figure 8 The TEM comparison of TAPP-Br nanosheets and bulk materials prepared in methanesulfonic acid aqueous solution. Compared with bulk material TAPP-Br, the nanosheets after peeling are significantly thinner and more transparent, indicating that the present invention successfully prepared thinner nanosheets.
[0057] Fig. 9 This is a comparison of the dispersion of bulk materials H2P-Bph-COF, TAPP-H, TAPP-Br, TAPP-OMe and TAPP-OH in methanesulfonic acid aqueous solution and pure water. The five bulk materials, two-dimensional porphyrin covalent organic frameworks, have poor dispersion in pure water, but turn green and have good dispersion in methanesulfonic acid. This is because the basic nitrogen atom in the porphyrin center can accept acidic protons, and when the porphyrin ring accepts positive ions from the acid, it turns green.
[0058] Fig.10 The FT-IR spectra of protonated TAPP-OMe and its bulk material prepared in methanesulfonic acid aqueous solution are compared. It can be seen from the figure that the characteristic peak of the imine bond is weakened after protonation, while the peak at 1670 cm -1 There is a new C=N + The stretching vibration peaks indicate that the protonation site is on the imine N.
[0059] Fig.11 The UV-visible absorption spectrum of protonated TAPP-OMe prepared in methanesulfonic acid aqueous solution. Compared with the bulk material, the peak intensity of the UV-visible absorption peak at around 426nm increased and shifted after protonation, and two new UV-visible absorption peaks appeared at 337nm and 648nm. This indicates that the two N atoms in the porphyrin center are positively charged after protonation.
[0060] The above embodiments describe the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the scope of the principles of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of protection of the present invention.
Claims
1. A method for liquid phase exfoliation of two-dimensional porphyrin covalent organic framework nanosheets by protonation strategy, characterized in that The specific steps are: placing the bulk material two-dimensional porphyrin covalent organic framework in a methanesulfonic acid aqueous solution for water bath ultrasonic liquid phase exfoliation, and then centrifugally washing and drying the dispersion to obtain a two-dimensional porphyrin covalent organic framework nanosheet, wherein the bulk material two-dimensional porphyrin covalent organic framework is H2P-Bph-COF, TAPP-H, TAPP-Br, TAPP-OMe or TAPP-OH, and the corresponding structural formula is:
2. The method for liquid phase exfoliation of two-dimensional porphyrin covalent organic framework nanosheets by protonation strategy according to claim 1, characterized in that: The feeding ratio of the block material two-dimensional porphyrin covalent organic framework and the methanesulfonic acid aqueous solution is 1 mg: 1-1.2 mL, and the concentration of the methanesulfonic acid aqueous solution is 0.6-1 mol / L.
3. The method for liquid phase exfoliation of two-dimensional porphyrin covalent organic framework nanosheets by protonation strategy according to claim 1, characterized in that: The temperature of the water bath ultrasonic liquid phase stripping is 20-30°C.
4. The method for liquid phase exfoliation of two-dimensional porphyrin covalent organic framework nanosheets by protonation strategy according to claim 1, characterized in that: The ultrasonic power of the water bath ultrasonic liquid phase stripping is 280-400W, and the ultrasonic time is 5-11h.
5. The method for liquid phase exfoliation of two-dimensional porphyrin covalent organic framework nanosheets by protonation strategy according to claim 1, characterized in that: The centrifugal washing comprises two processes: low-speed centrifugal washing and high-speed centrifugal washing. The centrifugal speed of the low-speed centrifugal washing is 1500-2500 rpm, the centrifugal time is 5-15 min, the centrifugal washing is performed 2-3 times, and the centrifugal washing solvent is a mixed solvent of water and ethanol. The upper layer of dispersion liquid is taken for high-speed centrifugal washing again. The centrifugal speed of the high-speed centrifugal washing is 10000-20000 rpm, the centrifugal time is 3-10 min, and the centrifugal washing solvent is a mixed solvent of water and ethanol. The bottom precipitate is collected and washed with secondary water for at least 10 times and with ethanol for at least 3 times to remove residual methane sulfonic acid. Finally, the washed precipitate is vacuum dried at 30-50° C. to obtain a pure two-dimensional porphyrin covalent organic framework nanosheet.
Citation Information
Patent Citations
Preparation method for graphene and graphene / OPBI composite material
CN105129784A
Covalent organic framework (COF) nanoparticles and preparation method thereof
CN114539547A
Preparation method of two-dimensional laminar covalent organic framework membrane
CN106512754A
Efficient preparation method of boron nitride nanosheet and organic dispersion liquid thereof
CN106586979A